(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
Eight modern wheat varieties (viz., Sourav, Gourab, Shatabdi, Sufi, Bijoy, Prodip, BARI Gom-25 and BARI Gom-26) were evaluated to find out the suitable variety for optimum and late sown condition, to find out heat tolerant and heat sensitive variety and to find out the optimum sowing time for a specific variety. The experiment was conducted in the research farm of Wheat Research Center (25°38´ N, 88°41´ E and 38.20 m above sea level.), Bangladesh, under eight sowing times (viz., 8 Nov., 15 Nov., 22 Nov., 29 Nov., 6 Dec., 13 Dec., 20 Dec. and 27 Dec.). Results showed that wheat sown in November 22 to December 20 was significantly better compared to November 08, 15 and December 27, from the studied aspects of yield and yield components. Considering overall sowing performance of all genotypes Shatabdi is the best, followed by BARI Gom-26 (2nd), Sourav (3rd), Prodip (4th), Bijoy (5th), Gourab (6th), Sufi (7th) and BARI Gom-25 (least). In extremely heat stress (November 08 and December 27) condition Prodip was found to be heat sensitive genotype (yield reduction 41.18 and 28.92%), followed by BARI Gom-26 (yield reduction 41.15 and 22.73%). Both in too early and very late heat stress conditions, genotypes Sourav and BARI Gom-25 were found to be heat tolerant. In very early (November 08), variety Sourav (yield reduction 20.47%) is recommended, followed by BARI Gom-25 (yield reduction 27.91%) and in very late (December 27), Sufi is the best (yield reduction 8.60%), followed by Bijoy (yield reduction 11.05%). DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13932 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 44-54, December, 2011